På råbeafstand af marxismen. Et bidrag til kritik af kritikken af kritikken (Latour, Foucault, Marx) - Bolt, Mikkel (K&K - Kultur og Klasse, 2016)
In the last couple of decades, critique has come in for a heavy beating: Critique is based on problematic notions of depth and exposure where the critic takes up a position of critical distance that presumes mastery over the material by revealing hidden depths beneath the surface. This article traces significant episodes in the development of this anti-critical critique by embedding it in a longer historical trajectory that has to do with an initially internal Marxist self-critique that paves the way for a downright dismissal of Marxism and the critical analysis of the capitalist mode of production. The article moves backward starting with Bruno Latour and his analysis of critique’s collapse to Michel Foucault and his complicated relationship to Marx and Marxism, ending with a call for a return to an analytic position that is in shouting distance to Marxism.